2021
DOI: 10.5194/bg-2021-268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of Rare Earths and associated major and trace elements during Douglas-fir (Pseudotsuga menziesii) and European beech (Fagus sylvatica L.) litter degradation

Abstract: Abstract. Given the diverse physico-chemical properties of elements, we hypothesize that their incoherent distribution across the leaf tissues, combined with the distinct resistance to degradation that each tissue exhibits, leads to distinct turnover rates between elements. Moreover, litter layers of different ages produce diverse chemical signatures in solution during the wet degradation. To verify our hypothesis, Na, K, Mg, Mn, Ca, Pb, Al and Fe were analysed together with the Rare Earth Elements (REE) in th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…All the REEs showed strong and significant positive increases both in concentration and amount with accumulated mass loss (Figures 4, 6). Few other short-term (Tyler, 2005;Gautam et al, 2020;Montemagno et al, 2021) as well as long-term (Brun et al, 2008) studies have reported an increase in REEs with the progression of decomposition. The increase probably is related to their immobilization and accumulation in the decomposing litter (Laskowski et al, 1995;Lomander and Johansson, 2001).…”
Section: Rare Earth Element (Ree) Dynamics During Decompositionmentioning
confidence: 95%
See 4 more Smart Citations
“…All the REEs showed strong and significant positive increases both in concentration and amount with accumulated mass loss (Figures 4, 6). Few other short-term (Tyler, 2005;Gautam et al, 2020;Montemagno et al, 2021) as well as long-term (Brun et al, 2008) studies have reported an increase in REEs with the progression of decomposition. The increase probably is related to their immobilization and accumulation in the decomposing litter (Laskowski et al, 1995;Lomander and Johansson, 2001).…”
Section: Rare Earth Element (Ree) Dynamics During Decompositionmentioning
confidence: 95%
“…Their encumbered behavior followed by enrichment can be related to the build-up of organic matter in the litter bags. A number of studies have linked the REE enrichment of litter to biological, chemical, and/or physical processes (Brun et al, 2008;Gautam et al, 2020;Montemagno et al, 2021). Microbes that contribute to litter decomposition have the capacity to render REEs immobilized in their biomass.…”
Section: Rare Earth Element (Ree) Dynamics During Decompositionmentioning
confidence: 99%
See 3 more Smart Citations